2018
DOI: 10.14744/anatoljcardiol.2018.38228
|View full text |Cite
|
Sign up to set email alerts
|

Low free triiodothyronine is associated with contrast-induced acute kidney injury and long-term outcome in elderly patients underwent percutaneous coronary intervention

Abstract: Objective: Low free triiodothyronine (fT 3 ) is common in elderly patients with cardiovascular disease. The purpose of this study was to evaluate the relationship between low fT 3 and contrast-induced acute kidney injury (CI-AKI), including the long-term outcomes, in elderly patients after a percutaneous coronary intervention (PCI). Methods: A total of 350 patients aged ≥75 years who underwent PCI between January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Combined with our results, CI-AKI is more likely to occur in the elderly and in patients with poor basal renal function. Consistent with our study, it is also reported that free triiodothyronine had a negative association with CI-AKI in patients undergoing primary PCI therapy (6,21). Preoperative hypotension may affect renal perfusion and lead to a higher risk of CI-AKI.…”
Section: Discussionsupporting
confidence: 90%
“…Combined with our results, CI-AKI is more likely to occur in the elderly and in patients with poor basal renal function. Consistent with our study, it is also reported that free triiodothyronine had a negative association with CI-AKI in patients undergoing primary PCI therapy (6,21). Preoperative hypotension may affect renal perfusion and lead to a higher risk of CI-AKI.…”
Section: Discussionsupporting
confidence: 90%
“…Another study by Zhang D et al [18] including 1339 patients in the general intensive care units demonstrated that when Cystatin C (Cys C) was used for detecting early AKI, FT3 was found to be independently associated with Cys C. Furthermore, FT3 had no significant impact on the diagnostic and predictive accuracy of Cys C in detecting AKI in ICU patients. A more recent study by us firstly investigated the relationship between FT3 concentration and CI-AKI in patients aged > 75 years undergoing PCI, which showed the incidence of CI-AKI was about 1.4 folds higher in patients with low FT3 compared with normal FT3, suggesting low FT3 might be a novel risk factor for CI-AKI [31]. It's well-known that low FT3 is more frequent in critical ill patients such as myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the elevation of serum creatinine has occurred in patients receiving contrast media 21 . Elderly patients have a higher incidence of CA‐AKI than younger adults, and older age is a risk factor for CA‐AKI in patients after PCI 22–24 . There are several reasons for the high rate of AKI in the elderly after PCI compared to that in young people: the elderly have more complex coronary artery lesions than the younger population, and older people will undergo more complicated procedures than was the case in the past 25 .…”
Section: Discussionmentioning
confidence: 99%
“… 21 Elderly patients have a higher incidence of CA‐AKI than younger adults, and older age is a risk factor for CA‐AKI in patients after PCI. 22 , 23 , 24 There are several reasons for the high rate of AKI in the elderly after PCI compared to that in young people: the elderly have more complex coronary artery lesions than the younger population, and older people will undergo more complicated procedures than was the case in the past. 25 In addition, aging causes changes in renal function (increased renal excretion of sodium and water).…”
Section: Discussionmentioning
confidence: 99%